Comparison of non-overlapping maize populations of unequal sizes for resistance to maize lethal necrosis - Awata, Luka A. O.; Ifie, Beatrice E.; Danquah, Eric; Tongoona, Pangirayi; Mahabaleswara, Suresh L.; Gowda, Manje; Marchelo-Dragga, Philip W.; Sitonik, Chelang’At; Olsen, Michael; Boddupalli, P.M.; Jumbo, McDonald Bright (Informa UK Limited, 2022)
Contrast between marker-assisted backcross (MABC) and doubled haploid (DH) methods in transferring genes for resistance to maize lethal necrosis (MLN) in maize (Zea mays L.) is not well understood. The MLN is caused by co-infection of maize plant by maize chlorotic mottle virus and sugarcane mosaic virus. Two maize panels consisting of four BC3F2 and six DH populations, separately developed through marker-assisted selection from crosses between susceptible CIMMYT lines and MLN-resistant donor parent (KS23-6), were used in the current study. The two populations were of different population structures with unequal sizes. Experiments were conducted under artificial MLN inoculations for two seasons in 2018. Analyses of variance revealed significant variations among genotypes in both panels (p ≤ 0.001). Levene’s and Welch’s tests found that variances and means of the BC3F2 and DH populations were highly unequal (p ≤ 0.001). The study identified genotypes with reduced MLN infections in both populations; however, lower means for MLN severity and area under disease progress curve (AUDPC) values, and higher heritability estimates were obtained in the DH populations than in the BC3F2 populations. Additionally, the DH populations showed higher relative genetic gains for resistance to MLN compared with the BC3F2 populations. The current study detected superiority of DH over MABC populations for breeding for resistance to MLN. Nevertheless, the results observed in the present study warrant further investigations using the same genetic materials with identical population sizes.